2019
DOI: 10.3389/fmicb.2019.00175
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Gut Microbiota in Dihydrotestosterone-Induced PCOS Rats and the Pharmacologic Effects of Diane-35, Probiotics, and Berberine

Abstract: Polycystic ovary syndrome (PCOS) is a frequent endocrine and metabolic syndrome in reproductive-age women. Recently, emerging evidence has shown that gut microbiota is closely related to metabolic diseases such as type 2 diabetes, obesity and PCOS. In the present study, we established dihydrotestosterone (DHT)-induced PCOS rats and used Illumina MiSeq sequencing (PE300) to examine the composition, diversity, and abundance of the gut microbiota in PCOS. We compared the effects of three PCOS treatments: Diane-35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 64 publications
2
49
2
1
Order By: Relevance
“…Liu et al found a decrease in Ruminococcaceae and an increase in gram-negative bacteria, including Bacteroides and Desulfovibrio, in women with PCOS, which was consistent with our research (20). Regarding to the phylum level of the gut microbiota, we found that the abundances of Firmicutes, Bacteroidetes, and Proteobacteria were the most dominant in all groups, in consistence with previous studies (12,77). An increase in Firmicutes/Bacteroidetes ratio is closely related to obesity (12,78).…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al found a decrease in Ruminococcaceae and an increase in gram-negative bacteria, including Bacteroides and Desulfovibrio, in women with PCOS, which was consistent with our research (20). Regarding to the phylum level of the gut microbiota, we found that the abundances of Firmicutes, Bacteroidetes, and Proteobacteria were the most dominant in all groups, in consistence with previous studies (12,77). An increase in Firmicutes/Bacteroidetes ratio is closely related to obesity (12,78).…”
Section: Discussionsupporting
confidence: 92%
“…Combination of Diane-35 and metformin treatment could decrease the BMI and LU levels, improve the condition of hyperandrogenemia and insulin resistance in PCOS patients [5]. In the dihydrotestosterone-induced PCOS rats, Diane-35 was found to be effective to restore the reproductive functions [17]. Consistently, in the present study, we found that combination of Diane-35 and metformin treatment reduced body weight, decreased the levels of testosterone and luteinizing hormone and insulin resistance, and also restored the estrous cycle and ovulation in the PCOS rats, indicating that the combined treatment improved the PCOS complications.…”
Section: Discussionmentioning
confidence: 97%
“…* p < 0.05, ** p < 0.01. S1), which tended to be flat when the sequences number increases to 8,429, showing that the amount of sequencing data were reasonable. The whole composition bacterial community was analyzed using Unweighted-Unifrac of Pcoa ( Fig.…”
Section: Inulin and Metformin Modulated Gut Microbiota In Pcosmentioning
confidence: 90%
“…The severity of insulin resistance and menstrual disorders as well as high levels of androgens in patients with PCOS are closely linked to alteration of gut microbiota [6]. A high fat diet and hyperandrogenic state induce LPS production from abnormal gut microbiota, causing systemic and ovarian inflammation in PCOS [7,8].…”
mentioning
confidence: 99%